ANALISIS KUALITAS KOMPOS DARI CAMPURAN TANDAN KOSONG KELAPA SAWIT DENGAN KOTORAN AYAM MENGGUNAKAN LIMBAH CAIR PABRIK KELAPA SAWIT DAN EM-4 - Suherman, Irawati; Awaluddin, Amir; ', Itnawita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Empty fruit bunches (EFB) are solid wastes produced in large quantity from palm oil industry. Thus, the wastes could cause serious problem to environment. The application of EFB as main component for composting process along with chicken dung is desirable. This research used the EFB combined with chicken dung, POME (Palm Oil Mill Effluent) and EM-4 in order to accelerate the composting process. Control’s sample was made using POME as an activator without EM-4. Quality of compost was determined according to its pH, water content and C/N ratio at each 5 days for 30 days composting period. The water content from the samples were determined using gravimetric method while total of N were determined using Kjehdal method. The result showed that co-composting of EFB and chicken dung using POME and EM-4 as the activators didn’t have significance difference on the control’s sample with the value of P>0,05. Meanwhile, the value of pH, water and C/N ratio of composting products were respectively 7, 40-50% and 17-19 after 30 days composting period